Drilling-based measuring method of rock strength through the IDE intelligent system - Wang, Qi; Ma, Fenglin; Gao, Hongke; Jiang, Bei; Bian, Zhenguo (Bulletin of engineering geology and the environment, 2025)
Compressive strength is a fundamental parameter characterizing the mechanical properties of rock. Its accurate determination serves as a prerequisite for stability analysis of surrounding rock and rational design of support systems in underground engineering. Digital drilling technology provides an innovative approach to in situ assessment of rock compressive strength. To implement this methodology, a quantitative relationship model between compressive strength and drilling parameters must be established, supported by the development of a dedicated field digital drilling test system. In this study, a mechanical analysis of rock rotary drilling is conducted and the relationship between drilling parameters and unit cutting energy is established. Using the newly developed rotary cutting test system for rock mass (RCT system), a series of rock drilling tests are conducted, the response of drilling parameters to the rock compressive strength is analyzed, and the drilling-based rock compressive strength inversion model (DP- σ c model) is established. Experimental results demonstrate an average deviation of 7.27% between the DP- σ c model predictions and laboratory uniaxial compression test results. Additionally, the intelligent drilling explore system of geology (IDE system) for field applications is developed. Stratified rock drilling tests conducted with the IDE system reveal its capability to effectively identify lithological interfaces, with an average discrepancy of 9.40% between predicted compressive strength values and laboratory measurements. These results validate both the accuracy of the DP- σ c model and the reliability of the IDE system. The study establishes a theoretical basis and technical support for in-situ rock strength assessment.